Methodological considerations in PISCES 3: a randomized, placebo-controlled study of intracerebral stem cells in subjects with disability following an ischemic stroke - Laskowitz, Daniel T.; Muir, Keith W.; Savitz, Sean I.; Wechsler, Lawrence R.; Pilitsis, Julie G.; Rahimi, Scott Y.; Beckman, Richard L.; Holmes, Vincent; Chen, Peng R.; Juel, Laura; Koltai, Deborah; Kolls, Brad J. (Frontiers in Stroke, 2023)
Background and Hypothesis: At present, there are no medical interventions proven to improve functional recovery in patients with subacute stroke. We hypothesize that the intraparenchymal administration of CTX0E03, a conditionally immortalized neural stem cell line, linked with a standardized rehabilitation therapy regimen for the upper limb, would improve functional outcomes in patients 6-12 months after an index ischemic stroke. Study Design: PISCES III was designed as a multicenter prospective, sham-controlled, outcome-blinded randomized clinical trial. Eligibility required a qualifying ischemic stroke 6-12 months prior to surgical intervention. Patients must be between 35 and 75 years of age and have residual moderate or moderately severe disability (mRS 3 or 4), with the preservation of some residual upper limb movement. All patients received a standardized regimen of home physical therapy following the intervention. Study Outcomes: The primary outcome measure is improvement in the modified Rankin Scale (mRS) of disability at 6 months post treatment. Secondary outcomes include assessment of activities of daily living (Barthel Index), functional mobility (Timed Up and Go; Fugl Meyer Assessment), neurological impairment (NIHSS), upper limb function (Chedoke Arm and Hand Inventory), as well as patient related quality of life and global rating scales. Discussion: PISCES III was designed as a randomized trial directly comparing the effects of intraparenchymal injection of a conditional stem cell line vs sham procedure in patients with subacute stroke. This is one of the first studies of this type to include a standardized minimum rehabilitation protocol. As there are a limited number of studies evaluating invasive stem cell administration in the chronic setting of CNS injury, study design considerations are discussed.